The oxidative stress is typical peculiarity by multiple sclerosis - N. V. Krotenko; V. M. Alifirova; S. A. Ivanova (Бюллетень сибирской медицины)
The problem of pathogenesis of multiple sclerosis is of great importance in modern neurology and its solution allows to determine a pathogenetic approach to treatment of this severe disease. Complex clinical-biochemical investigation has been conducted in 79 patients with multiple sclerosis and 75 mentally and physically healthy persons. Parameters of intensification of lipid peroxidation and indices of the state of enzymatic and non-enzymatic patterns in antioxidant defense system in different clinical forms and at different stages of MS course have been analyzed. The data obtained confirm the presence of oxidant stress in the development of pathological process in MS.